Pensamento sistêmico : os dilemas da educação superior - Olivera, Raul Angel Carlos (2013)
The choice of this research - SYSTEMIC APPROACH: The Dilemmas of Higher Education - is the result of a set of reflections and experiences collected over the past 6 years, in the course of practical activities in teaching, research and management positions at the University of the State of Mato Grosso -Unemat. During this period it was observed that education is seen as a component of human capital and universities are under pressure to become instruments for social inclusion at the same time their micro and macroeconomic efficiency is required in an increasingly restriction environment of funding public higher education because of budget deficits . The claim of higher education as a state policy and the concept of higher education as a national system is paradoxical when one realizes that the university can no longer perform their duties precisely because the functions given to it by society . The need to find mechanisms and alternatives to overcome the obstacles and dilemmas that crosses the university is the focus of this research. The research was developed taking as object of study the University of the State of Mato Grosso seen that since its inception it has undergone structural change according to the circumstances and needs . The discussions around the Unemat seems to hide contradictory interests from part of all segments of the academic community, even outside the community. Only this argument would justify the research. The methodological procedures for this research are mainly based on the study of references pertaining to General Systems Theory, economic theories of education, public policy analysis and theories of education. According to the target of the study, this work is a combination of an exploratory, descriptive and explanatory research with the purpose to provide familiarity with the problem. We start from the observation that whatever the reason, the crisis at the Unemat is more noticeable because it is in process of affirmation as a university. The systemic approach can help us in understanding the phenomena that take place outside the sphere of the individual if we believe that universities can be described as organizations working system of education that perform specific operations through which the educational system performs its function within the system society. For all this reason, it is very important to understand the mechanisms that determine the operation of the subsystem where knowledge is the central object. Education does not take only one way, but can take different forms according to the degree of development of the group. The search for how to handle the transmission of knowledge will gradually leading to the institution of ways to that goal.